AN ERROR ANALYSIS ON OUTGOING E-MAILS IN USING PLURAL FORM OF NOUNS (A CASE STUDY OF FRONT OFFICE DEPARTMENT AT ATTA MESARI VILLAS UBUD - I Gusti Ayu Agung Yuni Lestari; I Gusti Ngurah Bagus Yoga Widiadnya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2021)
In linguistics, grammatical number is a grammatical category of nouns, pronouns, and adjective and verb agreement that expresses count distinctions. English and other languages present number categories of singular or plural. In the hospitality industry, there are many kinds of English terms used by the staffs. This study was designed to find an error in used plural form of noun in Atta Mesari Villas Ubud by the Staff and this study employed a qualitative method. The subject of this study is the staff of Front Office department. The data were obtained through collecting data randomly for 30 outgoing emails at 2018 and review of the documents. According to the result of simple statistical calculation it is obtained the type of Error in Omission 52%, and Misformation 42% while the lowest error in addition is 6%.